A educação estatística crítica no quinto ano do ensino fundamental - Hollas, Justiani (2025)
This thesis presents research on Critical Statistical Education, accompanied by an Educational Product consisting of a teaching sequence developed for fifth-grade mathematics classes. The central question guiding the study is: how can we promote statistics teaching in fifth-grade elementary school from a critical perspective? The overall objective of this research is to develop, implement, and analyze a proposal for teaching statistics in fifth-grade elementary school through a teaching sequence that aligns with the theoretical and epistemological assumptions of Critical Statistical Education. From a methodological perspective, this is qualitative research, grounded in Didactic Engineering, as outlined by Artigue (1996). The research sought to meet the following specific objectives: to historically situate the teaching of statistics; to understand the theoretical foundations that underpin this field of teaching; to develop a teaching sequence for fifth-grade elementary school students; and to deepen the understanding of statistical literacy and critical thinking among students. The study emphasizes the fundamentals of statistics teaching, especially in the early years of elementary school, highlighting the importance of addressing the content from the initial stages of schooling. Concurrently, an Educational Product was developed. After implementing the proposal, data analysis was conducted using Discursive Textual Analysis, according to the methodology proposed by Moraes and Galiazzi (2007), using logbooks, video recordings, and photographs as collection tools. The developed Educational Product is presented throughout the thesis and made available as supplementary material, functioning as an additional resource to the textbook, aiming to support teachers in planning and implementing statistics classes. The research is considered a significant contribution to students' critical thinking and to the development of their ability to read the world, especially in the context of the transition between the early and late years of elementary school, a moment considered a significant milestone in basic education. Furthermore, the developed teaching sequence strengthens pedagogical practices and provides theoretical and methodological support to teachers with a degree in Pedagogy. All materials produced are available on the website of the Graduate Program in Science and Mathematics Teaching at the University of Passo Fundo (https://www.upf.br/ppgecm/dissertacoes-eteses/teses), as well as on the Educapes Portal (http://educapes.capes.gov.br/handle/capes/1174657), ensuring public access and the potential dissemination of research results and products.